Curious caterer : 3-movie collection [videorecording (DVD)]. - Davidson, Diane Mott (Hallmark Movies & Mysteries, 2024)
Dying for Chocolate: A Colorado caterer and single mom, Goldy Berry teams with detective Tom Schultz to identify the ingredients that led to the mysterious death of her friend - and ends up discovering a hidden recipe for murder. Grilling Season: Caterer Goldy Berry reunites with Detective Tom Schultz when a realtor is murdered. As they uncover personal and professional rivalries, they realize the culprit is closer than expected. Fatal Vows: In the third movie of the series, Goldy Berry, a caterer, and amateur detective, is recruited to provide food for a sizable wedding. Jessamyn Cole, the bride, is the ex-wife of Goldy's current love interest, detective Tom Schultz.